Stability of pedalling mechanics during a prolonged cycling exercise performed at different cadences - Sarre, G.; Lepers, R.; van Hoecke, J. (Journal of Sports Sciences, 2005)
The aim of this study was to analyse the effect of pedalling rate on the pattern of mechanical torque application and on neuromuscular fatigue during prolonged cycling exercise. Eleven well-trained individuals performed three 1-h pedalling sessions, at 50 rev·min-1, 110 rev·min-1 and a freely chosen cadence, at an intensity corresponding to 65% of their maximal aerobic power. The mechanical torque applied on the right pedal was recorded for 30 s every 5 min while pedalling. Contractile and neural properties of the quadriceps and hamstring muscles were analysed before and immediately after each of the three pedalling sessions. The post-exercise reduction in knee extensors maximal voluntary contraction was significant (P <0.01) irrespective of the cadence, but no difference was found between cadences. The use of a particular cadence did not lead to preferentially central or peripheral fatigue. An increase in cadence resulted in greater positive and negative work generated during pedalling. The mechanical pattern was not altered during the exercise, whatever the selected cadence. The present study demonstrates that despite the occurrence of neuromuscular fatigue, trained individuals maintained a stable pedalling pattern throughout an endurance cycling exercise for cadences ranging from 50 to 110 rev·min-1.